O CENTENÁRIO DA INDEPENDÊNCIA NO ACRE: ANACRONISMOS, UFANISMOS E COMEMORAÇÕES - Francisco Bento da Silva (Muiraquitã, 2022)
This article aims, from some hemerographic sources, to establish an analytical debate around the celebrations of the centenary of the so-called Independence of Brazil that took place in the Federal Territory of Acre in 1922. In cities such as Rio Branco, Sena Madureira, Cruzeiro do Sul, Xapuri and Tarauacá, the local authorities of the city halls together with the Territory government, organized various festivities in celebration of the independence which sought to enhance the civic spirit of youth, the patriotic duty of the authorities, an alleged historical common past and the feeling of national unity. For the dialogue with empirical sources, authors such as Benjamin (2013); Chauí (2000); Rancière (2011); Hobsbawm (1990), among others, helped us to think about aspects related to anachronism, ufanismo, patriotism and celebrations.